The Impacts of Flattening Fiscal Reform on Health Expenditure in China - Hao, Jun; Tang, Chengxiang; Zhu, Junli; Jiang, Jiayi (Frontiers in Public Health, 2021)
Introduction: A number of provinces have implemented a fiscal reform of flattening government since the first decade of this century in China. This study aims to quantitatively analyze the influences of this government fiscal reform on county-level health expenditure. We also bring forward policy suggestions for improving county-level fiscal system and healthcare delivery. Methods: We collected a novel longitudinal county-level data from 2003 to 2010, including counties' socioeconomic data, fiscal revenue, and health expenditure. Jilin Province, Hebei Province, and Anhui Province were selected as representative samples for this policy evaluation. The study employed a time-varying difference-in-difference model specification to investigate the impacts of flattening fiscal reform on health expenditure. Results: The analyses find that the fiscal system reforms of the three provinces have a significantly positive impact on the health expenditure of county-level governments. However, we find no policy effects on the proportion of health expenditure to fiscal expenditure of county-level governments. The estimation results are robust after controlling several background variables. Conclusion: The results yield important policy insights that public finance and its reform significantly impacts health expenditures in China. The government may still need to strengthen the transfer payment system to guarantee the social welfare provision in healthcare.